Accounting: Basic Principles./ Accounting: Principles and Applications. (Book). - Dockweiler, Raymond C.; Spiller, Earl A. (The Accounting Review, 1975)
Reviews two books "Accounting: Basic Principles," 3rd ed. and "Accounting: Principles and Applications," 3rd ed., by Horace R. Brock, Charles E. Palmer and Fred C. Archer.